Paradoks Digitalisasi Peradilan: Kajian Konstitusional Penerapan E-Court terhadap Asas Access to Justice dan Kepastian Hukum dalam Perkara Perdata - Dwi Maharani; Muhamad Afif Fathul Falah; Ardi Rizqi Kurniawan; Eksanudin Eksanudin; Tegar Harbriyana Putra (Res Publica: Jurnal Hukum Kebijakan Publik, 2026)
The digital transformation of the judiciary through the e-Court policy in Indonesia aims to realize the principles of speedy, simple, and low-cost justice as a manifestation of the constitutional right to access to justice. However, its implementation has engendered a fundamental paradox that threatens legal certainty and the principle of equality before the law. This study is premised on the assertion that digitalization must not be reduced to mere bureaucratic automation, but must be directed toward the fulfillment of human rights. This article aims to critically examine the paradox of judicial digitalization and reconstruct the e-Court policy to align with distributive justice in the era of disruption. Employing a normative legal research methodology, this study utilizes statute and conceptual approaches, subjected to systematic analysis. The analytical framework is constructed upon Cappelletti and Garth’s third-wave Access to Justice theory and Jeremy Bentham’s utilitarianism, to evaluate whether technology-driven procedural reforms have dismantled structural barriers and maximized utility. The findings reveal that although the e-Court offers administrative efficiency, it is hindered by a digital infrastructure divide, low digital literacy, the lack of integrated civil registry data, and designs that remain inaccessible to persons with disabilities. Empirical data indicating low e-litigation adoption rates in remote areas corroborates the existence of significant access disparities. Consequently, a reconstruction of the e-Court policy is imperative, necessitating a paradigm shift from mere digital efficiency to constitutional digital justice. This reconstruction demands the strengthening of inclusive infrastructure, the harmonization of procedural laws concerning electronic evidence, the implementation of affirmative policies, and the enhancement of digital legal literacy, thereby transforming the e-Court into a robust instrument for the democratization of justice.